2014
DOI: 10.1039/c4cc05295a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide membranes with tunable permeability due to embedded carbon dots

Abstract: In this communication, we fabricated graphene oxide membranes with tunable permeation by embedding carbon nanodots of controllable sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 32 publications
0
92
0
2
Order By: Relevance
“…From all these observations, it is evident that these types of graphene oxide membranes are suitable candidates for an effective desalination application. Li et al [61] in their recent work reported carbon dots impregnated graphene oxide membrane as an effective tunable permeation system. According to Li et al [61], the purpose of embedding the carbon dots in the interspaces is to tune the spacing and channels that exist between graphene oxide layers.…”
Section: Go Membrane As Ionic and Molecular Sieve In Solutionmentioning
confidence: 98%
See 2 more Smart Citations
“…From all these observations, it is evident that these types of graphene oxide membranes are suitable candidates for an effective desalination application. Li et al [61] in their recent work reported carbon dots impregnated graphene oxide membrane as an effective tunable permeation system. According to Li et al [61], the purpose of embedding the carbon dots in the interspaces is to tune the spacing and channels that exist between graphene oxide layers.…”
Section: Go Membrane As Ionic and Molecular Sieve In Solutionmentioning
confidence: 98%
“…Li et al [61] in their recent work reported carbon dots impregnated graphene oxide membrane as an effective tunable permeation system. According to Li et al [61], the purpose of embedding the carbon dots in the interspaces is to tune the spacing and channels that exist between graphene oxide layers. Further, Li et al [61] attributed that the compositional similarity between carbon dots and graphene oxide favoured a better distribution of carbon dots than any other nanomaterials on to the graphene oxide and thereby an excellent compatible permeation membrane has emerged.…”
Section: Go Membrane As Ionic and Molecular Sieve In Solutionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, such an approach does not compromise the rejection efficiency of the membrane for pollutants such as organic dyes. 69,70 In practice, challenges and solutions. Although numerous studies have shown the applicability of this class of membranes for water desalination, in particular as NF membranes, many studies in the literature have addressed current challenges.…”
Section: Multilayer Graphene Desalination Membranesmentioning
confidence: 99%
“…The 2D nanosheets produced through the exfoliation of bulk layered materials can restack to be lamellar membranes, and excellent water permeance and unwanted species rejection can be achieved by tuning the interlayer spacing between contiguous nanosheets . For instance, graphene oxide (GO) based membranes, which were widely investigated as 2D membranes, have shown potential application in water treatment owing to their unique molecule‐sieving performance combined with fast water permeation . Because of the presence of nanocapillary channels, GO lamellar membranes can selectively allow the permeation of water as well as sieving of dye molecules and hydrated ions .…”
Section: Introductionmentioning
confidence: 99%